Optimal identification of Be-doped Al0.29Ga0.71As Schottky diode parameters using Dragonfly Algorithm: A thermal effect study. (December 2021) - Filali, Walid; Amrani, Rachid; Garoudja, Elyes; Oussalah, Slimane; Lekoui, Fouaz; Oukerimi, Zineb; Sengouga, Nouredine; Henini, Mohamed
Abstract: In this work, a recent heuristic method called Dragonfly Algorithm (DA) has been employed for the first time to investigate the temperature effect on the Schottky diode electrical parameters. Beryllium-doped Al0.29 Ga0.71 As Schottky diodes grown by molecular beam epitaxy (MBE) have been used to validate the suggested method. The proposed approach is based on the analysis of current-voltage-temperature (I–V-T) and capacitance-voltage (C–V) characteristics. Furthermore, the interface state density ( N s s ) as function of the difference between the surface state energy and valence band energy ( E s s − E V ) was determined. The obtained results demonstrate the high efficiency of this strategy to accurately determine the electrical parameters and investigate their temperature dependency. This efficiency can be clearly remarked from the well fit between both predicted and measured current characteristics. Highlights: Current-voltage and capacitance-voltage characterization of Beryllium-doped Al0.29 Ga0.71 As Schottky diodes is carried out. A recent efficient optimization method called Dragonfly algorithm (DA) to determine the Schottky diodes parameters. The obtained results show the high efficiency and accuracy of the proposed method.